Silica Nanoparticles as a Probable Anti-Oomycete Compound Against Downy Mildew, and Yield and Quality Enhancer in Grapevines: Field Evaluation, Molecular, Physiological, Ultrastructural, and Toxicity Investigations - Rashad, Younes M.; El-Sharkawy, Hany H. A.; Belal, Bassam E. A.; Abdel Razik, Elsayed S.; Galilah, Doaa A. (Frontiers in Plant Science, 2021)
Downy mildew is the most destructive disease of grapevines in the regions of relatively warm and humid climate causing up to 50% yield losses. Application of silicon-based products has been extensively studied against various oomycete, fungal, bacterial, and viral plant diseases, but studies on Si application in their nano-size are limited. In this study, field application of silica nanoparticles (SiNPs) was evaluated on Thompson Seedless grapevines (H4 Strain) infected with downy mildew. In addition, molecular, physiological, ultrastructural, and toxicity investigations were also conducted. The obtained results revealed that spraying of grapevines with SiNPs at 150 ppm significantly overexpressed the transcription factor JERF3 recording 8.7-fold, and the defense-related genes β-1,3-glucanase (11-fold), peroxidase (10.7-fold) pathogenesis-related-protein 1 (10.6-fold), and chitinase (6.5-fold). Moreover, a reduction up to 81.5% in the disease severity was achieved in response to this treatment. Shoots length and yield per grapevine were considerably enhanced recording up to 26.3 and 23.7 % increase, respectively. The berries quality was also improved. Furthermore, this treatment led to an enhancement in the photosynthetic pigments, induction of phenolic and ascorbic acid contents, increase in activity of peroxidase and polyphenol oxidase enzymes, and reduction in the cellular electrolyte leakage, lipid peroxidation, and H2O2 content. Scanning electron microscopy observations showed an increase up to 86.6 % in the number of closed stomata and a reduction up to 55 % in the average stomatal pore area in response to this treatment. Observations of the transmission electron microscopy showed ultrastructural alterations in cells of grapevine leaf due to infection with downy mildew including plasmolysis and disruption of the cellular components, abnormal chloroplasts, and thickening of the cell wall and cell membrane. These abnormal alterations reduced in response to SiNPs spray. In contrast, the study showed also that this treatment had considerable cytotoxic and genotoxic effects at this direct dose/concentration. So, additional investigations to determine the SiNPs residue in the produced edible plant parts are urgently needed. In addition, the pre-harvest interval, toxicity index, and risk assessment should be evaluated before any recommendation for use.